Impact of sirolimus treatment for refractory kaposiform hemangioendothelioma with exacerbation of the disease 10 years after initial diagnosis. (28th May 2018) - Sakata, Naoki; Suenobu, So-ichi; Okano, Munehiro; Ueda, Satoshi; Kimura, Masatomo; Takemura, Tsukasa
We describe our experience with a 12 year-old girl with kaposiform hemangioendothelioma accompanied by Kasabach–Merritt phenomenon with exacerbation of the disease 10 years after the initial diagnosis. Kaposiform hemangioendothelioma infiltrated into the subcutaneous tissue of the facial skin with deterioration of coagulopathy despite conventional therapies including corticosteroid, vincristine, and propranolol. Sirolimus, a mammalian target of rapamycin inhibitor, produced rapid and dramatic improvement of the Kasabach–Merritt phenomenon and kaposiform hemangioendothelioma shrinkage. Eventually, multifocal lesions of kaposiform hemangioendothelioma disappeared on the images of magnetic resonance imaging and have remained in remission for 27 months after sirolimus cessation. We demonstrated that the AKT/mammalian target of rapamycin signaling pathway played a pivotal role in the kaposiform hemangioendothelioma growth. Sirolimus must be a strong candidate for molecular therapy targeting kaposiform hemangioendothelioma.